The relationship of fasting hyperglycemia to changes in fat and muscle mass after exercise training in type 2 diabetes. (December 2016) - Yalamanchi, Swaytha V.; Stewart, Kerry J.; Ji, Nan; Golden, Sherita H.; Dobs, Adrian; Becker, Diane M.; Vaidya, Dhananjay; Kral, Brian G.; Kalyani, Rita R.
Abstract: Aims: Exercise training (ET) has been variably associated with body composition changes among persons with type 2 diabetes (T2DM). The degree to which these changes are related to hyperglycemia remains unclear. Our objective was to investigate the relationship of baseline fasting glucose (FG) to the magnitude of muscle gains and fat loss after ET in individuals with T2DM. Methods: Participants were enrolled in the SHAPE-2 trial, a six month supervised aerobic and resistance training intervention (three days/week), at Johns Hopkins. This was a post hoc single arm intervention study of participants who completed the exercise intervention ( n = 50). Participants were aged 40–65 years and had T2DM that was not treated with insulin. Body composition was assessed by DEXA. Results: After 6 months of ET, total fat mass decreased (−2.1 ± 3.1 kg) and total lean body mass (LBM) increased (0.5 ± 2.0 kg) overall, but there was variability among individual participants. There was an increase in % total LBM (1.4 ± 1.9%) and decrease in % total body fat mass (−1.5 ± 2.0%) after ET. Interestingly, each standard deviation (SD) increase in baseline FG (mean = 135.5 mg/dl; SD = 39.0 mg/dl) was related to a significant increase in % total LBM (0.54 ± 0.26%, p = 0.048) and decrease in % total body fat (−0.57 ± 0.27%, p = 0.04) after ET among individual participants. Conclusions: Our data demonstrate that muscle gains and fat loss after ET are positively related to baseline hyperglycemia. Further studies are needed to characterize differences in metabolic response following ET among persons with diabetes.